Entraves para a produção jornalística com perspectiva de gênero a partir da feminização do jornalismo no Brasil - SOUSA, Nayara Nascimento de (2022)
This research aims to analyze the factors that hinder the production of journalistic content with a gender perspective for women in Brazilian journalism, checking whether there are differences when considering education (individual dimension) and professionalization (organizational dimension). We are also interested in relating intersectional aspects, especially gender and race, in the phenomenon of the feminization of journalism, in addition to contributing to the production of data on the female profile in the area. The methodology used is a non-probabilistic quantitative survey, for women who work or have worked in journalism, provided they have some experience with journalistic production. The data were collected between June 2 and September 3, 2021, and we validated 217 respondents from all states of Brazil and the Distrito Federal. From the descriptive analysis, we have as main results: the profile of the respondents corroborates surveys with journalism professionals, being cis women, white, young, and with a high level of education. About education, the informants had little contact with issues related to gender during graduation. However, younger women indicated more access to these issues, which shows possible recent changes in Journalism courses. In relation to the work aspects, we verified a greater racial diversity among the women who work in consulting firms, while the media and the teaching profession seem to present greater barriers of access for non-white professional women. The main difficulty verified in approaching the gender perspective in the production refers to the organizational factor: the agendas billed as militancy constitute an obstacle, to the extent that gender is treated as a forbidden theme, strange to the work environment and without legitimacy in journalism. Finally, companies need vertical and horizontal changes, offering space and naturalizing discussions of this nature.